The cost of a small membrane bioreactor - Lo, C. H.; McAdam, Ewan; Judd, Simon J. (IWA Publishing, 2015)
The individual cost contributions to the mechanical components of a small membrane bioreactor (MBR) (100–2,500 m3/d flow capacity) are itemised and collated to generate overall capital and operating costs (CAPEX and OPEX) as a function of size. The outcomes are compared to those from previously published detailed cost studies provided for both very small containerised plants (<40 m3/day capacity) and larger municipal plants (2,200–19,000 m3/d). Cost curves, as a function of flow capacity, determined for OPEX, CAPEX and net present value (NPV) based on the heuristic data used indicate a logarithmic function for OPEX and a power-based one for the CAPEX. OPEX correlations were in good quantitative agreement with those reported in the literature. Disparities in the calculated CAPEX trend compared with reported data were attributed to differences in assumptions concerning cost contributions. More reasonable agreement was obtained with the reported membrane separation component CAPEX data from published studies. The heuristic approach taken appears appropriate for small-scale MBRs with minimal costs associated with installation. An overall relationship of net present value = (a tb)Q(−c lnt+d) was determined for the net present value where a = 1.265, b = 0.44, c = 0.00385 and d = 0.868 according to the dataset employed for the analysis.
Keywords: CAPEX; costs; membrane bioreactor; NPV; OPEX